THE RELATIONSHIP BETWEEN PARENTING PATTERN AND ADOLESCENT SMOKING BEHAVIOR - Djenaan, Dadang; Ponidjan, Tati Setyawati; Ransun, Djony (Jurnal Ilmiah Perawat Manado (Juiperdo), 2022)
Background: The behavior of adolescents is generally a period when adolescents want to be given the freedom to do whatever they want. The attitude of some Indonesian youths has assumed that smoking is a necessity that cannot be avoided and various other reasons make smoking a common thing. Parents' mistakes in implementing parenting styles can result in children acting as they please, not being able to control themselves, including smoking. Purpose: This research is to explain the relationship between parenting styles and adolescent smoking behavior. Methods: This study uses a type of literature review research, which is a study in the form of a literature review using the results of previous research or textbooks or research journals. To obtain data that is in accordance with the topic, the researcher conducted a national and international search for journals on two databases, namely Google Scholar and PubMed using the keywords parenting and adolescent smoking behavior, the researcher found 5 journals that matched the title of the researcher. Results: From a total of 5 journals, there was a relationship between parenting parents and smoking behavior in adolescents. Suggestion: Be more prepared regarding the availability of literature such as books, journals, and other literature so that in the process of working on a literature study you can discuss theory in depth. Keywords: Parenting patterns, smoking behavior